A thermoelectric voltage effect in polyethylene oxide - Martin, Björn; Wagner, Achim; Kliem, Herbert (Journal of physics. D, Applied physics, 2003)
The conductivity of polyethylene oxide (PEO) is described with a three-dimensional hopping model considering electrostatic interactions between the ions. Ions fluctuate over energy-barriers in a multi-well potential. To decide whether positive or negative charges are responsible for this conductivity, the thermoelectric voltage is measured. The samples are embedded between two aluminium-electrodes. The oxide on the interface between the electrodes and the PEO serves as a blocking layer. The temperature of each electrode is controlled by a Peltier element. A temperature step is applied to one electrode by changing the temperature of one of the Peltier elements. Due to this temperature gradient, the mobile charges fluctuate thermally activated from the warmer side to the colder side of the sample. The direction of the measured thermoelectric voltage indicates the type of mobile charges. It is found that positive charges are mobile. Further, it is shown that the absolute value of the thermoelectric voltage depends on the energy-barrier heights in the multi-well potential.
Gesehen am 14.01.2020